Effects of fipronil (active ingredient of Frontline (R)) on salivary gland cells of Rhipicephalus sanguineus females (Latreille, 1806) (Acari: Ixodidae) - Pereira, C. P. M. [UNESP]; Oliveira, P. R. [UNESP]; Furquim, K. C. S. [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, M. I. [UNESP] (Elsevier B.V., 2009)
The present study analyzed the effects of the chemical compound fipronil, active ingredient of Frontline(R) (acaricide and insecticide), on the salivary glands of unfed and semi-engorged female Rhipicephalus sanguineus; tick. Unfed females were only exposed to the concentration of 1 ppm of fipronil, while semi-engorged females were treated with fipronil in three concentrations: 1 ppm, 5 ppm, and 10 ppm (distilled water was used as control). The histological and histochemical results revealed significant changes caused by this compound in the morphology and physiology of the gland tissue of unfed and semi-engorged females. In unfed females, the morphological changes in type I acini were characterized by an increase in size and diameter of the lumen. These changes are probably associated with the excretory function, indicating that type I acini might be responsible for eliminating this xenobiotic from the system of the parasite. In semi-engorged females, fipronil did not interfere in the cell death, which in these individuals occurred by apoptosis. However, it accelerated salivary gland degeneration, as the extent of damage increased along with the concentrations of the product. Our results clearly showed that fipronil interferes with the process of engorgement in females that consequently is reflected in the reproductive process, decreasing or even halting egg laying, and resulting in less blood losses for the hosts and reducing the transmission of pathogens through these glands. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus sanguineus; Fipronil; Tick; Acaricide; Cytotoxic effect; Salivary gland